Gene Expression Profiling in the Injured Spinal Cord of Trachemys scripta elegans: An Amniote with Self-Repair Capabilities - Valentin-Kahan, Adrián; García-Tejedor, Gabriela B.; Robello, Carlos; Trujillo-Cenóz, Omar; Russo, Raúl E.; Alvarez-Valin, Fernando (Frontiers in Molecular Neuroscience, 2017)
Slider turtles are the only known amniotes with self-repair mechanisms of the spinal cord that lead to substantial functional recovery. Their strategic phylogenetic position makes them a relevant model to investigate the peculiar genetic programs that allow anatomical reconnection in some vertebrate groups but are absent in others. Here, we analyze the gene expression profile of the response to spinal cord injury (SCI) in the turtle Trachemys scripta elegans. We found that this response comprises more than 1000 genes affecting diverse functions: reaction to ischemic insult, extracellular matrix re-organization, cell proliferation and death, immune response and inflammation. Genes related to synapsis and cholesterol biosynthesis are down-regulated. The analysis of the evolutionary distribution of these genes shows that almost all are present in most vertebrates. Additionally, we failed to find genes that were exclusive of regenerating taxa. The comparison of expression patterns among species shows that the response to SCI in the turtle is more similar to that of mice and non-regenerative Xenopus than to Xenopus during its regenerative stage. This observation, along with the lack of conserved “regeneration genes” and the current accepted phylogenetic placement of turtles (sister group of crocodilians and birds), indicates that the ability of spinal cord self-repair of turtles does not represent the retention of an ancestral vertebrate character. Instead, our results suggest that turtles developed this capability from a non-regenerative ancestor (i.e. a lineage specific innovation) that was achieved by re-organizing gene expression patterns on an essentially non-regenerative genetic background. Among the genes activated by SCI exclusively in turtles, those related to anoxia tolerance, extracellular matrix remodeling and axonal regrowth are good candidates to underlie functional recovery.